2014
DOI: 10.1089/jcr.2014.0005
|View full text |Cite
|
Sign up to set email alerts
|

Subjective State, Blood Pressure, and Behavioral Control Changes Produced by an “Energy Shot”

Abstract: Background: Energy drinks and energy shots are popular consumer beverages that are advertised to increase feelings of alertness. Typically, these products include high levels of caffeine, a mild psychostimulant drug. The scientific evidence demonstrating the specific benefits of energy products to users in terms of subjective state and objective performance is surprisingly lacking. Moreover, there are rising health concerns associated with the use of these products. Therefore, the purpose of this study was to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 25 publications
1
31
0
2
Order By: Relevance
“…Several studies have shown that energy drinks exerted different effects on BP, but the use of different volumes and the concentration of components [16,21] or the fact that the beverages tested were prepared using only some of the components of the commercial brands [22] may be the reasons for this disagreement. However, some studies demonstrated an increase in SBP and DBP after energy drink intake [20,21], and one case of reversible hypertension induced by energy drinks was reported [47]. Caffeine promotes endothelial dysfunction and activates the sympathetic nervous system [48], which may generate the increase in BP values.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have shown that energy drinks exerted different effects on BP, but the use of different volumes and the concentration of components [16,21] or the fact that the beverages tested were prepared using only some of the components of the commercial brands [22] may be the reasons for this disagreement. However, some studies demonstrated an increase in SBP and DBP after energy drink intake [20,21], and one case of reversible hypertension induced by energy drinks was reported [47]. Caffeine promotes endothelial dysfunction and activates the sympathetic nervous system [48], which may generate the increase in BP values.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to inquire more profoundly about the multiple effects of energy drinks to determine more precisely the potential harmful actions and the real effects on mental and physical performance [20,22] to compare the results with the proclaimed effects [84], according with the existing evidence. This further research is fundamental to providing correct information to consumers, especially adolescents and their parents [6], including health science students, who should paradoxically become more aware of such information.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In agreement with the findings of our study (19) on the predominantly myocardial effects of sugar-sweetened EDs are the following: 1) a report that the consumption of a sugarsweetened Monster ED (Monster Beverage; 2.0 mg caffeine/kg and 0.65 g sugar/kg) significantly elevated heart rate after 60 min compared with the placebo control (20), 2) a study in which blood pressure and heart rate responses to a sugarsweetened ED (Rockstar, Rockstar, Inc.; 240 mg caffeine and ;62 g sugar) resulted in significantly elevated blood pressure values (systolic blood pressure: +6.6 mm Hg; diastolic blood pressure: +4.2 mm Hg) compared with a sugarmatched placebo (21), and 3) findings from current studies evaluating the impact of sugar-free caffeinated energy shots [5-h Energy; 200 mg and 215 mg caffeine] on cardiovascular variables that showed that blood pressure variables significantly increased whereas heart rate did not change (22,23). Moreover, repeated intakes of an ED [8.3 oz of a Red Bull ED (Red Bull GmbH) 4 times over 24 h; 1 oz = 30 mL] increased blood pressure variables when compared with a water drink with equivalent amounts of caffeine (8 oz water with 80 mg caffeine) (24).…”
Section: Eds and Hemodynamics: Overall Effectsmentioning
confidence: 97%
“…Expecting a possibly compensatory reduction in HR as a result of increased BP, the lowest available data point independent of time was extracted for the HR end point. [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] When multiple usable arms were available within an individual study, the data were counted as another study in the meta-analysis model. 19 This was done in parallel design studies only to avoid artificial sample size inflation.…”
Section: Data Extraction and Quality Assessmentmentioning
confidence: 99%